The scoring techniques in the final competitions of the karate World Championships 2016 - Alinaghipour, M.; Zareian, E.; Pooraghaei Ardakani, Z. (Annals of Applied Sport Science, 2020)
Background. Scoring is the main determinant factor for winning in any sport and good techniques can facilitate scoring. In Karate, there are series of punching and kicking techniques that fighters use for scoring. Objectives. The aim of this research was to determine the most scoring techniques and their frequencies in final kumite competitions of 2016 world karate championships. Methods. By the help of a video analysis software and a Microsoft excel sheet all the data referring to the scored techniques (by winners and losers" and their frequencies have been gathered and recorded. In overall, 10 Fights with total number of 70 scores were analyzed. The finalists used some predominant techniques in order to overcome their opponents. Results. By the help of a video analysis software and a Microsoft excel sheet all the data referring to the scored techniques (by winners and losers" and their frequencies have been gathered and recorded. In overall, 10 Fights with total number of 70 scores were analyzed. The finalists used some predominant techniques in order to overcome their opponents. Conclusion. This shows that speed and explosive power is an indication in recent karate especially in the world-class level and karatekas.